Comparative analysis of storage systems in collection centers: Impact on the quality of hard yellow maize in Quevedo and surrounding areas, Ecuador - Beltrán-Chacón, Jorge Patricio; Aguayo Carvajal, Verónica Rosalva (ECOAgropecuaria. Revista Científica Ecológica Agropecuaria, 2025)
Hard yellow maize constitutes a key element in the Ecuadorian agroindustry, especially in Quevedo and areas of influence such as Valencia, Buena Fe, and Mocache, where post-harvest losses due to storage deterioration affect the supply chain. This study adopts a mixed approach (quantitative-qualitative) to compare three storage systems: hermetic, ventilated, and traditional. In the quantitative aspect, 300 grain samples were collected to analyze moisture, insect damage, aflatoxin levels, and weight loss, employing ANOVA with Tukey's post-hoc test to identify significant differences. The qualitative component included 20 semi-structured interviews analyzed thematically. The results indicate that hermetic systems maintain moisture at 12.2 % and reduce insect damage by 80 %, while ventilated systems show intermediate values (13.5 % in moisture) and traditional systems record higher losses (up to 20 % due to infestations). Aflatoxin levels were low in hermetic systems (< 3 ppb), moderate in ventilated, and high in traditional. Qualitatively, economic barriers are identified, although benefits in quality are recognized. Consequently, hermetic systems could minimize losses by 30%, with recommendations for subsidies and training. This work addresses local gaps in post-harvest, providing data for policies in food processing.
Keywords: Agroindustrial losses; grain quality; maize storage; post-harvest losses; Quevedo; Ecuador; silos